Does Festival Quality Effect Psychological Well-being Through Festival Value and Festival Satisfaction? - Fadhilah Jihan Faezha; Titik Rosnani; Ramadania Ramadania; Heriyadi Heriyadi; Wenny Pebrianti (Komunitas Dosen Indonesia, 2024)
This study investigates the impact of festival quality on the psychological well-being of attendees at The Eras Tour in Indonesia, emphasizing the mediating roles of festival value and satisfaction. The background highlights the increasing significance of large-scale music events, which necessitate high-quality experiences to enhance attendee satisfaction and well-being. The research aims to explore how festival quality influences psychological well-being through perceived value and satisfaction. A questionnaire was administered to 190 Indonesian respondents who attended the concert, using a 5-point Likert scale for measurement. The analysis employed Partial Least Squares Structural Equation Modelling (PLS-SEM) to evaluate the relationships among variables. Results indicate that festival quality positively affects both festival value and psychological well-being, confirming that higher quality leads to greater perceived value and emotional responses. While festival satisfaction did not significantly mediate this relationship, festival value emerged as a crucial mediator. These findings suggest that enhancing festival quality can improve attendees' psychological well-being, offering practical implications for event organizers to focus on aspects such as venue selection and service quality to foster a more satisfying experience. Future research should explore the long-term effects of these variables and develop validated measurement scales for better empirical comparisons.